If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(9 + 6x) = -441 (9 * 7 + 6x * 7) = -441 (63 + 42x) = -441 Solving 63 + 42x = -441 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-63' to each side of the equation. 63 + -63 + 42x = -441 + -63 Combine like terms: 63 + -63 = 0 0 + 42x = -441 + -63 42x = -441 + -63 Combine like terms: -441 + -63 = -504 42x = -504 Divide each side by '42'. x = -12 Simplifying x = -12
| 4x-2(-2y+5x)+6y= | | 5y+8n= | | 6(-8-5x)=-168 | | 1=b/3-7 | | 5(x+1)-7.5x=-2 | | 8=192 | | -3/14y=-15 | | 0=-16t^2+160t+3 | | 81g=3564 | | 37t=3478 | | 8n-8m/16n-16m | | 56w=4648 | | 106=6x+7x+2 | | 60m=4020 | | 83j=5644 | | 8t(6t+2)+t(4t+3)= | | *2x-3**5x+6*= | | Log(X)9=(1/2) | | 11!11!/13!14! | | 3c+7.25=4.72 | | 74e=1258 | | 3w-18*w=244 | | -4(3+7x)=-180 | | n^2+15n+57=0 | | 17p=1326 | | 50k=2650 | | 1,816,168.016=4/3*3.14*x^3 | | 1,816,168.016=4/3*3.14*r^3 | | 36*67= | | 68a=3332 | | n^2+5n+1= | | 4cos(2x)=3 |